Evaluation of Funding Gastroenterology Research in Canada Illustrates the Beneficial Role of Partnerships. (2013) - Sherman, Philip M; Hart, Kimberly Banks; Rose, Keeley; Bosompra, Kwadwo; Manuel, Christopher; Belanger, Paul; Daniels, Sandra; Sinclair, Paul; Vanner, Stephen; Buret, André G
Abstract : BACKGROUND: Funders of health research in Canada seek to determine how their funding programs impact research capacity and knowledge creation. OBJECTIVE: To evaluate the impact of a focused grants and award program that was cofunded by the Canadian Institutes of Health Research Institute of Nutrition, Metabolism and Diabetes, and the Canadian Association of Gastroenterology; and to measure the impact of the Program on the career paths of funded researchers and assess the outcomes of research supported through the Program. METHODS: A survey of the recipients of grants and awards from 2000 to 2008 was conducted in 2012. The CIHR Funding Decisions database was searched to determine subsequent funding; a bibliometric citation analysis of publications arising from the Program was performed. RESULTS: Of 160 grant and award recipients, 147 (92%) completed the survey. With >17.4 million in research funding, support was provided for 131 fellowship awards, seven career transition awards, and 22 operating grants. More than three-quarters of grant and award recipients continue to work or train in a research-related position. Combined research outputs included 545 research articles, 130 review articles, 33 book chapters and 11 patents. Comparative analyses indicate that publications supported by the funding program had a greater impact than other Canadian and international comparators. CONCLUSIONS: Continuity in support of a long-term health research funding partnership strengthened the career development of gastroenterology researchers in Canada, and enhanced the creation and dissemination of new knowledge in the discipline.